1996
DOI: 10.1007/bf00041391
|View full text |Cite
|
Sign up to set email alerts
|

Sequence homology requirements for transcriptional silencing of 35S transgenes and post-transcriptional silencing of nitrite reductase (trans)genes by the tobacco 271 locus

Abstract: The transgene locus of the tobacco plant 271 (271 locus) is located on a telomere and consists of multiple copies of a plasmid carrying an NptII marker gene driven by the cauliflower mosaic virus (CaMV) 19S promoter and the leaf-specific nitrite reductase Nii1 cDNA cloned in the antisense orientation under the control of the CaMV 35S promoter. Previous analysis of gene expression in leaves has shown that this locus triggers both post-transcriptional silencing of the host leaf-specific Nii genes and transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…I transformed the parental line with pPZP200/ RB-masP-BAR-nosT-LB, in which the promoter is replaced with the Agrobacterium tumefaciens mannopine synthase promoter (masP), and found that all of the 295 T1 plants that showed resistance to glufosinate exhibited a level of de-etiolation that was typical of the parental plants (silencing rateϭ0%) (Figure 2). This finding is consistent with the previous observation that TGS can be reduced by using different promoters to drive the expression of each transgene (Neuhuber et al 1994;Thierry and Vaucheret 1996). Then, I replaced the nosT terminator with the Agrobacterium tumefaciens octopine synthase terminator (ocsT) to yield pPZP200/RB-p35S-BAR-ocsT-LB, and performed a similar analysis.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…I transformed the parental line with pPZP200/ RB-masP-BAR-nosT-LB, in which the promoter is replaced with the Agrobacterium tumefaciens mannopine synthase promoter (masP), and found that all of the 295 T1 plants that showed resistance to glufosinate exhibited a level of de-etiolation that was typical of the parental plants (silencing rateϭ0%) (Figure 2). This finding is consistent with the previous observation that TGS can be reduced by using different promoters to drive the expression of each transgene (Neuhuber et al 1994;Thierry and Vaucheret 1996). Then, I replaced the nosT terminator with the Agrobacterium tumefaciens octopine synthase terminator (ocsT) to yield pPZP200/RB-p35S-BAR-ocsT-LB, and performed a similar analysis.…”
supporting
confidence: 87%
“…In such cases, although the possibility cannot be excluded that post-transcriptional gene silencing (PTGS) that is based on homology in mRNA sequences may also be involved, the inactivation of the transgene is most likely due to transcriptional gene silencing (TGS), which occurs in the presence of sequence homology in the promoter regions that are used to overexpress a gene of interest in the first T-DNA and to express a selectable marker gene in the second T-DNA. Although TGS can be substantially reduced by using different promoters to drive the expression of each transgene (Neuhuber et al 1994;Thierry and Vaucheret 1996), a technique that completely prevents TGS is needed in order to facilitate large-scale genetic screens. In this study, I have developed a procedure to block TGS, while designing a large-scale genetic screen to identify downstream components of phytochrome B (phyB) signal transduction.…”
mentioning
confidence: 99%
“…A decade ago, we described a transgene locus that triggers both TGS and PTGS of diVerent targets (Elmayan and Vaucheret 1996;Thierry and Vaucheret 1996). The 271 locus consists of multiple copies of the tobacco nitrite reductase (NIR) sequence in antisense orientation (RIN) driven by the CauliXower Mosaic Virus (CaMV) 35S promoter and the bacterial neomycin phosphotransferase (npt) sequence driven by the CaMV 19S promoter.…”
Section: Introductionmentioning
confidence: 99%
“…The 271 transgenic tobacco line was regenerated from kanamycin-resistant callus that spontaneously became sensitive to kanamycin and was unable to grow on medium containing nitrate or nitrite as the sole source of nitrogen (Vaucheret et al 1992). The 271 locus was subsequently shown to silence, by TGS, any transgene driven by the 19S or 35S promoter and to silence, by PTGS, endogenous NIR genes as well as NIR transgenes (Elmayan and Vaucheret 1996;Park et al 1996;Thierry and Vaucheret 1996), indicating that the 271 locus is a universal silencer of 19S, 35S, and NIR sequences. The 271 locus, however, was unable to silence npt transgenes by PTGS, but only by TGS when they are driven by the 19S or 35S promoter.…”
Section: Introductionmentioning
confidence: 99%
“…As homology-dependent gene silencing of transgenes under control of the CaMV 35S promoter had previously been reported (e.g. Assaad et al, 1993;Thierry and Vaucheret, 1996), it was conceivable to find reduced expression of one or both HR genes in double-resistant plants. However, although the expression level of pat and cp4 epsps genes in single-resistant as well as in double-resistant plants varied with the developmental state of the plants and with temperature, the presence of an additional transgene in the LL × RR hybrids never resulted in transgene inactivation.…”
Section: Variation In Gene Expressionmentioning
confidence: 91%